The Costs and Benefits of Regulating the Market for Corporate Insolvency Practitioner Remuneration. Issue 1 (15th July 2015) - Dickfos, Jennifer
Abstract: The release by the Australian Treasury on Friday, 7 November 2014 of the Insolvency Law Reform Bill ( ILRB ) 2014 throws the spotlight once again on corporate insolvency law reform in Australia. Significantly, the ILRB 2014 identifies amongst its purposes two objectives with respect to Corporate Insolvency Practitioner (CIP) remuneration reform. Namely, to promote market competition on price and quality and improve the overall confidence in the professionalism and competence of insolvency practitioners. This paper considers whether the proposed CIP remuneration reforms outlined in the ILRB 2014 will effectively achieve these objectives. Where it is considered that reforms are misdirected, further changes, informed by UK insolvency reform proposals, are considered.